Polymer supported vanadium and molybdenum complexes as potential catalysts for the oxidation and oxidative bromination of organic substrates - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (Dalton Transactions, 2006)
{The Schiff base (H(2)fsal-ohyba) derived from 3-formylsalicylic acid and o-hydroxybenzylamine has been covalently bonded to chloromethylated polystyrene cross-linked with 5% divinylbenzene ( abbreviated as PS-H(2)fsal-ohyba, I). Treatment of [
Keywords: Bile acids; bis-steroids; hybrids; Peptides; polyamines; saponins; steroidal conjugates; synthetic ionophores

Synthesis and characterisation of polymer-anchored oxidovanadium(IV) complexes and their use for the oxidation of styrene and cumene - Maurya, Mannar R.; Kumar, Umesh; Manikandan, Palanichamy (European Journal of Inorganic Chemistry, 2007)
{The Schiff bases H(2)fsal-ea (I), H(2)fsal-pa (II) and H(2)fsal-amp (III), derived from 3-formylsalicylic acid and 2-aminoethanol, 3-aminopropanol and 2-amino-2-methylpropanol, respectively, have been connected, by means of covalent bonds, to chloromethylated polystyrene cross-linked with 5% divinylbenzene. On treatment with [
Keywords: dissolution rate; mass transfer coefficient; particle size distribution; polydisperse solid; reactive liquid

Extracellular bacterial synthesis of protein-functionalized ferromagnetic Co3O4 nanocrystals and imaging of self-organization of bacterial cells under stress after exposure to metal ions - Kumar, Umesh; Shete, Ashvini; Harle, Arti S.; Kasyutich, Oksana; Schwarzacher, W.; Pundle, Archana; Poddar, Pankaj (Chemistry of Materials, 2008)
Co3O4, which crystallizes in the spinet phase at temperatures much higher than ambient temperatures, orders antiferromagnetically below its Neel temperature (similar to 40 K). However, in nanosize, it shows ferromagnetic ordering due to surface canting, disorder, imperfect oxygen atom coordination, etc. Here, for the first time, we report the synthesis of single-crystalline, ferromagnetic Co3O4 nanoparticles functionalized with proteins (size 5-7 nm) using cobalt acetate as precursor at room temperature in aqueous medium by a metal-tolerant marine bacterium isolated from the coast of the Arabian Sea. Energetically unfavorable change in the oxidation state of Co atoms from (+2 to +3) during synthesis by the bacterial strain was evidenced by X-ray photoelectron spectroscopy. The effect on the morphology of bacterial cells after exposure to the cobalt acetate was imaged by scanning electron microscopy showing cooperative, self-organized. structured colony formation, possibly due to the interbacterial communication under external stress.

Human blood vessel-derived endothelial progenitors for endothelialization of small diameter vascular prosthesis - Ranjan, Amaresh K.; Kumar, Umesh; Hardikar, Ashutosh A.; Poddar, Pankaj; Nair, Prabha D.; Hardikar, Anandwardhan A. (Plos One, 2009)
Background: Coronary bypass graft failure as a result of acute thrombosis and intimal hyperplasia has been the major challenge in surgical procedures involving small-diameter vascular prosthesis. Coating synthetic grafts with patients' own endothelial cells has been suggested to improve the patency rate and overall success of bypass surgeries. Methodology/Principal Findings: We isolated endothelial progenitor cells (EPCs) from leftover pieces of human saphenous vein/mammary artery. We demonstrate that EPCs can be expanded to generate millions of cells under low-density culture conditions. Exposure to high-density conditions induces differentiation to endothelial cell phenotype. EPC-derived endothelial cells show expression of CD144(high), CD31, and vWF. We then assessed the ability of differentiated endothelial cells to adhere and grow on small diameter expanded polytetrafluoroethylene (ePTFE) tubings. Since ePTFE tubings are highly hydrophobic, we optimized protocols to introduce hydrophilic groups on luminal surface of ePTFE tubings. We demonstrate here a stepwise protocol that involves introduction of hydrophilic moieties and coating with defined ECM components that support adhesion of endothelial cells, but not of blood platelets. Conclusion/Significance: Our data confirms that endothelial progenitors obtained from adult human blood vessels can be expanded in vitro under xenoprotein-free conditions, for potential use in endothelialization of small diameter ePTFE grafts. These endothelialized grafts may represent a promising treatment strategy for improving the clinical outcome of small-caliber vascular grafts in cardiac bypass surgeries.

Mechanistic study of surface functionalization of enzyme lysozyme synthesized Ag and Au nanoparticles using surface enhanced raman spectroscopy - Das, Raja; Jagannathan, Ramya; Sharan, Chandrashekhar; Kumar, Umesh; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
The fate of bioactivity of biomolecules such as enzymes, proteins, and even drug molecules is greatly affected by the conformational changes in the proximity of the solid surfaces. This interaction is the key to the potential of their further applications as biosensors, in drug delivery, etc. With increasing interest in the biofunctionalization of noble metal nanoparticles for various applications, it is important to precisely investigate the functional groups responsible for binding with the nanoparticle surfaces and probable structural changes in the structure of the biomolecules as both are key factors affecting the bioactivity of these molecules once they are tagged onto the nanoparticle surfaces. However, it is not an easy task to probe these properties, especially for bigger Molecules such as enzymes and proteins. Surface-enhanced Raman spectroscopy (SERS) has been used extensively in the detection of biomolecules and study of their conformation on noble metal surfaces since its discovery because of its high sensitivity. This technique is capable of detecting changes in the secondary structure and the effects of surrounding environment on the biomolecule in the proximity of nanoscopic rough metal surfaces. In this study, we have used this technique to precisely determine the functional groups responsible in the Surface capping of Ag and Au nanoparticles synthesized by the hen egg derived enzyme lysozyme. The sharp and intense Stokes Raman shift peaks observed around 704, 866, 1519, and 1598 cm(-1), in the case of Ag nanoparticles, which are assigned to tryptophan, tyrosine, phenylalanine, and histidine residues, clearly indicate the involvement of these residues for surface passivation of the Ag nanoparticle surface. The Ag-N peak situated around 236 cm(-1) was also seen in the spectra, showing that probably the amine group of lysozyme is responsible in binding to the Ag nanoparticle surface. Similarly, in the case of Au nanoparticles, we observed sharp and intense peaks around 1583, 1545, and 1584 cm(-1) which were assigned to above-mentioned amino acid residues, indicating that a similar mechanism is also responsible for the binding of lysozyme molecules at the Au nanoparticle surface. In both cases peaks for the amide III band (C-N-H) around 1250 cm(-1) were also observed.

Real-time nanomechanical and topographical mapping on live bacterial cells-brevibacterium casei under stress due to their exposure to Co2+ Ions during microbial synthesis of Co3O4 nanoparticles - Kumar, Umesh; Vivekanand, K.; Poddar, Pankaj (Journal of Physical Chemistry B, 2009)
The study of elastic properties of microbial and mammalian cells using atomic force microscopy, with force-sensitivity as high as pico-Newtons and spatial resolution of a few nanometers, is proving to be a great tool for the real-time observation of the effects of drugs, biomolecules, metal ions, and nanoparticles on cell physiology in their natural environment. It has been shown that the Young's modulus of the cell surfaces is extremely sensitive to the surrounding environment. Recently, a broad array of microbes have been used successfully to synthesize nanocrystals of several metal and metal oxides in a controlled manner at room temperature after exposing them to various metal ion precursors. However, so far there is no report on the fate of their elastic properties and cell topography etc. during and after their exposure to the metal ions during the microbial synthesis of nanomaterials. Additionally, this information is also found to be extremely relevant to areas such as bioremediation, bioleaching, and biomineralization, where it is important to study the direct influence on the cell physiology in the presence of metal ions. Here, we report, for the first time, the use of AFM force-distance curves on live cells, to directly monitor (in real time) the changes in the surface-topography, surface-adhesion, indentation-depth, and Young's modulus of a metal-tolerant marine bacterium, Brevibacterium casei, isolated from the coast of the Arabian Sea, after its exposure to the Co2+ ions during the process of biosynthesis of nanoparticles. We earlier reported that this bacterium is capable of using the cobalt acetate as a precursor to synthesize protein-functionalized Co3O4 nanoparticles with very high crystallinity. Our study indicates a significant change in the morphology as well as elastic and adhesive properties of the Brevibacterium casei, where we found an increase in the adhesive properties and the indentation depth of the bacterial surfaces and a decrease in the cell stiffness after several hours of exposure to the cobalt acetate. We have discussed both qualitative and quantitative analysis of the force-spectroscopy data in detail.

Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver